PENGARUH PENGAJARAN BERBASIS TEKNOLOGI INFORMASI TERHADAP KOMPETENSI GURU SMK DI WILAYAH PARUNG PANJANG, KABUPATEN BOGOR, JAWA BARAT - Sudarso, Aden Prawiro (JGK (Jurnal Guru Kita), 2020)
Abstract: The Effect of Information Technology-Based Teaching on the Competence of Vocational School Teachers in Parung Panjang, Bogor Regency, West Java. The purpose of this study was to analyze the effect of information technology-based teaching on the competence of study teachers at Vocational High Schools in Parung Panjang. Bogor Regency. West Java The method used is explanatory research where the population is all Vocational High School (SMK) teachers in the Parung Panjang area. Bogor Regency. West Java, as many as 165 teachers. While in taking the sample, the writer used the Slovin formula with an error level of 5% where after calculating the number of samples obtained were 117 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study PBTI variable obtained an average score of 3.98 with good criteria. The teacher competency variable obtained an average score of 4.06 with good criteria. The statistical test on the structure-1 model obtained tcount> ttable (4.002> 1.98) and Sig 1.98) dan Sig < 0.05 (0.000 < 0.05). Hasil ini mengartikan variabel PBTI berpengaruh positif dan signifikan terhadap kompetensi guru.Kata Kunci: Pengajaran Berbasis Teknologi Informasi, Kompetensi Guru.